SYSTEMATIC LITERATURE REVIEW (SLR) : Teknologi dalam Pembelajaran Matematika selama Satu Dekade Terakhir - Kurniati, Ratnah; Sugiarto, Sigit; Lestari (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2023)
The use of technology in learning Mathematics in the current digital era is very important. However, knowledge about technology in Mathematics learning is still lacking for the majority of teaching staff. Therefore, it is important to conduct basic research regarding technology in teaching Mathematics. This research is a literature review that aims to review articles about Technology in Mathematics Learning which includes applications, software, platforms, and online course providers used in Mathematics learning. The articles reviewed are English-language articles published from 2013 to 2022 on the Springer database. The process of determining the articles analyzed in this study used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) principles. Based on the results of the analysis, it was obtained: 1) the highest distribution of article publications in 2022, namely 24 articles; 2) the most widely used technologies (applications, software, platforms and online course providers) are GeoGebra and Video (animated videos, learning videos, and video tutorials), Digital Games and Intelligent Tutoring Systems (ITS); 3) the most articles, namely articles with 3 authors, 23 articles; 4) that the countries with the most researchers conducting research on technology in teaching mathematics are the USA and UK with respective percentages of 35.06% and 12.99%; and 5) The publisher that publishes the most articles about technology in Mathematics learning is Digital Experiences in Mathematics Education. Researchers recommend conducting meta-analysis research on the impact of using technology on Mathematics learning.